Development of a HOTS-Based Science Learning Implementation Plan (RPP) in Primary Schools Using the TPACK Approach on Blood Circulatory System Material - Dyna Nurmalita Sari; Nana Hendracipta; A Syachruroji (Journal of Education Technology Information Social Sciences and Health, 2024)
This development research aims to develop, determine the feasibility, and determine students' responses to the development of a HOTS-based science learning implementation plan (RPP) in elementary schools using the TPACK approach on human circulatory system material. The method used is the Research and Development (RD) research method with a modified Sugiyono research and development model, namely: (1) Problem Analysis, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Revision Design, (6) Product Testing. Data collection techniques in this research used interviews in needs analysis, assessment questionnaires from several experts in the field of RPP assessment and LKPD assessment to determine product suitability, as well as class V student response questionnaires. The research results were based on the average value of the validation test results for the RPP assessment. 90.0% received the very appropriate category, and the validation test results for the LKPD assessment were 89.0% in the very appropriate category, as well as student responses with results of 86.91% in the very good category. Based on these results, the product in the form of a HOTS-Based Science Learning Implementation Plan (RPP) in Elementary Schools with the TPACK Approach on Human Circulatory System Material is suitable for use in the learning process of students in class V of elementary school.